PENGUJIAN DAYA BERKECAMBAH BENIH DAN EVALUASI STRUKTUR KECAMBAH BENIH - Elfiani, Elfiani; Jakoni, Jakoni (DINAMIKA PERTANIAN, 2017)
Testing germination in principle is to test a number of seeds and determine the percentage of seeds that can grow or be able to germinate normally at the specified time period. This test aimed to learn how to test a variety of seeds and germination of seeds of a particular lot by using a paper substrate, assessing different types of seeds that germinated species and classify them, determine the viability of a seed lot with benchmark germination. Tests on rice seed germination showed that seeds still qualify for graduation certification under the provisions established by the Directorate General of Food Crops for germination percentage above 80%. In addition, the percentage growth rate (KCT) is also quite high which indicates that the seed is still vigor. Benih corn and soybean seed were tested did not meet the graduation requirement of certification of seeds but the percentage growth rate (KCT) each classified as still having medium and high vigor. Germination in spinach showed that seeds still qualify for graduation certification. Evaluation of two maize seed lots showed normal germination percentage significantly. Quality tested physiological soybean seed has declined, by looking at the percentage of normal seedling is quite low and the percentage of dead seeds are quite high.